PROFESIONALISME PENGELOLAAN KEUANGAN DI DESA BIAU KECAMATAN BIAU KABUPATEN GORONTALO UTARA - Umar Sako Baderan (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2025)
This study aims to determine the professionalism of financial management in Biau Village, Biau District, North Gorontalo Regency. Research methods using qualitative types. The results showed that the professionalism of financial management in Biau Village was not optimal. 4 (four) indicators that have been used as a benchmark for research have not been fulfilled, this can be seen from the knowledge indicator, namely there are still apparatuses who do not understand the rules and duties as implementers of village financial management, skill indicators, namely there are still village apparatuses who are not proficient in using computer technology and operating the siskeudes application, ability indicators, namely overall financial management can be completed but in a way Individuals still have some apparatus who have not been able to complete their tasks so that they are still assisted by other apparatuses, and indicators of experience (experience) are all previous apparatuses no one is experienced and self-taught and has not maximized technical training on village financial management.